2015
DOI: 10.1136/thoraxjnl-2014-206689
|View full text |Cite
|
Sign up to set email alerts
|

Computerised clinical decision support for suspected PE: Table 1

Abstract: This study aimed to determine the effect of an evidence-based clinical decision support (CDS) algorithm on the use and yield of CT pulmonary angiography (CTPA) and on outcomes of patients evaluated in the emergency department (ED) for suspected PE. The study included 1363 consecutive patients evaluated for suspected PE in an ED during 12 months before and 12 months after initiation of CDS use. Introduction of CDS was associated with decreased CTPA use (55% vs 49%; absolute difference (AD), 6.3%; 95% CI 1.0% to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 4 publications
2
28
0
Order By: Relevance
“…19,21 The diagnostic yield, measured before intervention to diminish overuse, varied from 4.7% to 31%. 7,19 If the European study is removed, however, the range for the baseline volume of imaging is 7.4 to 26.5, and the diagnostic yield range is 4.7% to 12%. 7,18,21,23…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19,21 The diagnostic yield, measured before intervention to diminish overuse, varied from 4.7% to 31%. 7,19 If the European study is removed, however, the range for the baseline volume of imaging is 7.4 to 26.5, and the diagnostic yield range is 4.7% to 12%. 7,18,21,23…”
Section: Resultsmentioning
confidence: 99%
“…Eight of the studies appraised CDS interventions. 13,16,17,19,21,22,24,28 They consisted of computer-based applications imbedded into the computerized physician order entry of the setting (ED or clinical ward of an acute care hospital), which are prompted when a physician orders an imaging exam or D-dimer test.…”
Section: Cds and Pfrsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Studies in adult EDs have demonstrated that EHRlinked CDS improved adherence to guidelines and outcomes for a variety of emergent conditions. [26][27][28] Despite the need to standardize care and limit radiation exposure in children with possible appendicitis, we are not aware of any published EHR-linked tools to guide ED clinicians in the evaluation and management of this patient population. In the current study, we developed, implemented, and evaluated the safety and effectiveness of a novel EHR-linked CDS tool for patients with suspected appendicitis within a large Midwestern pediatric hospital system.…”
mentioning
confidence: 99%
“…demonstrated an increase in CTPA from 8.1% to 10.6% with Wells score based clinical decision support while Jimenez et al . demonstrated a significant decrease in CTPA use via the introduction of computer‐based diagnostic decision support although they did not see a corresponding increase in imaging yield . Internationally, adoption of an age‐adjusted D‐dimer compared with a flat cut‐off of 0.5 mg/L has been shown to safely increase the diagnostic yield of D‐dimer testing and overall imaging yield, although Jones et al .…”
Section: Discussionmentioning
confidence: 96%